A Feasibility Study on Monitoring Residual Sugar and Alcohol Strength in Kiwi Wine Fermentation Using a Fiber‐Optic FT‐NIR Spectrometry and PLS Regression. Issue 2 (19th January 2017) - Wang, Bingqian; Peng, Bangzhu
Abstract: This work aims to investigate the potential of fiber‐optic Fourier transform‐near‐infrared (FT‐NIR) spectrometry associated with chemometric analysis, which will be applied to monitor time‐related changes in residual sugar and alcohol strength during kiwi wine fermentation. NIR calibration models for residual sugar and alcohol strength during kiwi wine fermentation were established on the FT‐NIR spectra of 98 samples scanned in a fiber‐optic FT‐NIR spectrometer, and partial least squares regression method. The results showed that R 2 and root mean square error of cross‐validation could achieve 0.982 and 3.81 g/L for residual sugar, and 0.984 and 0.34% for alcohol strength, respectively. Furthermore, crucial process information on kiwi must and wine fermentations provided by fiber‐optic FT‐NIR spectrometry was found to agree with those obtained from traditional chemical methods, and therefore this fiber‐optic FT‐NIR spectrometry can be applied as an effective and suitable alternative for analyses and monitoring of those processes. The overall results suggested that fiber‐optic FT‐NIR spectrometry is a promising tool for monitoring and controlling the kiwi wine fermentation process.